DESIGNING AN ESD-INTEGRATED DIGITAL LEARNING ENVIRONMENT FOR ENHANCING SUSTAINABILITY CONSCIOUSNESS IN ELEMENTARY SCIENCE EDUCATION - Miar Zakira; Erna Suhartini; Mustamiroh Mustamiroh; Muhlis Muhlis (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
The current digital era demands that education continually keep pace with technological advances. One area that can be developed is a digital module, also known as an e-module. A digital module is a collection of non-printed, computer-based learning resources designed and used efficiently for classroom teaching. Differentiated learning is urgently needed to support current learning in accordance with sustainable education, which aligns with the 2030 SDGs agenda related to Education for Sustainable Development (ESD). This study employs a Research and Development (R&D) approach, utilizing the ADDIE model of development. The research subjects consisted of 78 fifth-grade students from SDN 011 in Samarinda City. Data collection techniques were carried out through observation and questionnaires. Data were collected through needs analysis questionnaire sheets, student characteristics analysis questionnaire sheets, needs analysis observation sheets, media expert questionnaire sheets, material expert questionnaire sheets, student response questionnaire sheets, teacher response questionnaire sheets, and sustainable awareness questionnaire sheets. Validation results showed the media was highly suitable, with scores of 93.2% from material experts, 87.8% from media experts, 88.82% from teacher responses, and 93.3% from student responses. Researchers recommend that module developers consider Canva's various features when developing digital modules to make them more engaging and innovative. Future researchers are expected to integrate ESD with other learning materials and media